PEMANFAATAN APLIKASI ONESEARCH.ID DI UNIVERSITAS UDAYANA - Satryawibawa, Kadek Darmayuda; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 1 (2022), 2022)
The goal of this study was to determine the use of the Onesearch.id application at Udayana University. This research method is descriptive quantitative and data collection techniques using a questionnaire. The population in this study is the academic community of Udayana University. The sample uses the Slovin formula and the sampling technique is purposive sampling. Based on the results of the analysis, it shows that the Onesearch.id application is used by students as a learning aid, improves student performance, increases student effectiveness, makes it easier to make assignments, easy to learn, easy to understand and flexible when used by students, very fun, the Onesearch. id is very safe, and students are eager to return to using the Onesearch.id application. Keywords : Digital Libraries, Applications, Onesearch.id, Universities